EFFECT OF CLASSICAL AYURVEDIC TREATMENT IN THE FUNCTIONAL IMPROVEMENT OF PATIENTS WITH RHEUMATOID ARTHRITIS (AYUSHDHARA, 2017)
Arthritis and various musculoskeletal disorders are the leading causes of disability in persons between 18 to 65 years of age and are common causes of disability related to employment. Among them Rheumatoid arthritis is a common clinical condition characterized by pain, stiffness and inflammation of joints with varying degree of disability. In this study 50 patients (age group between 20-60 yrs) diagnosed as RA after assessing both objective and subjective parameters have undergone the prescribed classical Ayurvedic treatments, both IP and OP level to evaluate its effect in the functional improvement. The study period was totally 57 days which includes 21 days each at inpatient and outpatient basis and 15 days of follow up. Initial course was Ama pachana treatments for 7 days. It includes Pachana medicines internally and Ruksha pottali sweda externally. Next 14 days, Samana medicines internally and Pathra pottali sweda externally were given. Same internal medicines and oil application were continued for next 21 days as outpatient. The response of treatment was assessed periodically with respective parameters and were showed significant effect. The improvement in functional assessment evaluated by using the Das 28 score, disability index, quality of life index -SF36 and global assessment of disease activity scale are all found significant changes. The lab parameters used to evaluate the liver and kidney function did not show any adverse changes that shows the prescribed treatment is safe.